ECOPRENEURSHIP IN ASIA: A BIBLIOMETRIC ANALYSIS OF SUSTAINABLE INNOVATION RESEARCH TRENDS - Muhyi, Herwan Abdul; Sukmadewi, Rani; Chan, Arianis; Rivani, Rivani; Kahfi, Arbi Abdul (Universitas Padjadjaran, 2025)
The accelerating environmental crisis has driven the emergence of Ecopreneurship as a transformative approach that integrates business innovation with environmental responsibility and social sustainability. Asia, as the world’s fastest-growing economic region, faces critical environmental challenges while simultaneously fostering a new generation of sustainable entrepreneurs. This study aims to map scientific research trends and identify future directions in Ecopreneurship studies in Asian countries through a bibliometric analysis based on the Scopus database, covering the period from 2002 to August 2025. Using the PRISMA method for systematic screening, 561 articles were analyzed and visualized using VOSviewer to identify thematic clusters, publication trends, and research collaborations. The results reveal a significant surge in publications since 2014, coinciding with the implementation of the Sustainable Development Goals (SDGs) and the Paris Agreement. China and India dominate publication output, followed by Malaysia and Indonesia, reflecting Southeast Asia’s growing academic engagement in sustainable entrepreneurship. Seven major keyword clusters were identified, spanning individual-level factors (e.g., motivation, self-efficacy), organizational strategies (e.g., green innovation, sustainability orientation), and macro-level issues (e.g., policy, social entrepreneurship). The findings indicate that Ecopreneurship research in Asia is increasingly multidisciplinary, incorporating digital technologies such as artificial intelligence (AI) and the Internet of Things (IoT) to advance the green economy. This study contributes by providing a comprehensive overview of research evolution, identifying key gaps, and outlining future research directions. In particular, it highlights the need for deeper investigation into digital integration, policy frameworks, and multi-level interactions among individual, organizational, and ecosystem factors to strengthen sustainable entrepreneurship in Asia.